A PRE EXPERIMENTAL STUDY IN TEACHING INFERENCE FROM SPOOF TEXT BY USING ERRQ READING STRATEGY - Septiani, Syarah; ., Sudarsono; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: This research was designed to answer the research questions about the significance and the size effect of the use of ERRQ reading strategy to teach inference making from spoof text. The sample was grade- XI IPA in SMA SANTUN UNTAN that consisted of thirty students. The data were collected by a multiple choice test and analyzed by t-test and size effect formula. The findings show that the use of ERRQ reading strategy increase students ability in inference-making significantly and the level of the effectiveness is classified as high. Key words: Teaching, Inference, ERRQ strategy, Spoof Abstrak: Penelitian ini dilakukan untuk menjawab pertanyaan penelitian mengenai signifikansi dan tingkat efektifitas dari penggunaan strategy membaca ERRQ dalam pengajaran memahami makna tersirat dari teks spoof. Sampel penelitian ini adalah kelas XI IPA SMA SANTUN UNTAN yang terdiri dari tiga puluh siswa. Data penelitian didapatkan dengan menggunakan tes pilihan ganda dan dianalisa menggunakan rumus t-test serta rumus tingkat efektifitas. Hasil penelitian menunjukan bahwa strategi membaca ERRQ meningkatkan kemampuan siswa dalam memahami makna tersirat secara signifikan dan diklasifikasikan tingkat efektivitasnya tinggi. Kata kunci: Mengajar, Makna Tersirat, Strategi ERRQ, Spoof